Formulation and Physical Test of Hair Tonic with Mangosteen Peel Extract (Garcinia mangostana L.) (Universitas Muhammadiyah Yogyakarta, 2025)
Hair Tonic is made from the extract of mangosteen peel (Garcinia mangostana L.) and other additional ingredients, which are beneficial in addressing hair loss and nourishing the hair. Scientifically, mangosteen fruit is known to contain Xanthones and flavonoids that function as antioxidants essential for hair health. These compounds can repair damaged hair cells and promote a conducive skin environment for hair growth. The research employed an experimental method involving the creation of four formulations. The mangosteen peel was extracted through maceration using ethanol as a solvent and then evaporated using a rotary evaporator. Subsequently, it was formulated into a Hair Tonic, and the formulation underwent evaluation. Data analysis was conducted through both qualitative and quantitative analyses. Qualitative analysis included organoleptic testing and homogeneity testing, while quantitative analysis involved pH testing, viscosity testing, specific gravity testing, and stability testing using the freeze-thaw cycling method. The results of the research on the organoleptic test for four formulations showed insignificant color differences, ranging from brown, light brown, and dark brown to transparent brown. Homogeneity evaluation indicates that concentration variations in the hair tonic do not affect the stability of its homogeneity. Observations of pH changes during the cycling test (cycles 1 to 6) show an increase in pH values but still within the standard limits. The viscosity values of the Hair Tonic before and after cycling comply with the standard. In conclusion, the overall physical characteristics of the Hair Tonic are that all formulations are suitable to be used, and all of them comply with the requirements.